2020
DOI: 10.3390/s20247189
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Guided Wave Directivity Patterns of Thin Removable Magnetostrictive Patches

Abstract: The characteristics of removable magnetostrictive thin patches are investigated for the generation of guided waves in plates. The directivity patterns of SH, S0 and A0 modes have been measured in a thin metallic plate for different combinations of static and dynamic magnetic field directions. This used different coil geometries such as racetrack and spiral coils to generate the dynamic magnetic field, as well as separate biasing static magnetic fields from permanent magnets. This arrangement generated signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Previous work by the authors has established some of the operating conditions that result from these configurations [ 23 , 24 ], including the radiation patterns of the A0, S0 and SH0 guided wave modes. In Configuration 1, no significant Lorentz forces were expected, leaving only magnetostrictive forces as the driving mechanism.…”
Section: Choice Of Magnet and Coil Configurationsmentioning
confidence: 99%
“…Previous work by the authors has established some of the operating conditions that result from these configurations [ 23 , 24 ], including the radiation patterns of the A0, S0 and SH0 guided wave modes. In Configuration 1, no significant Lorentz forces were expected, leaving only magnetostrictive forces as the driving mechanism.…”
Section: Choice Of Magnet and Coil Configurationsmentioning
confidence: 99%
“…The magnetostrictive patch used in the experiments was fabricated from a VACOFLUX 48 iron–cobalt alloy supplied by ® VACUUMSCHMELZE GmbH & Co., Hanau, Germany, with the dimensions and properties given in Table 1 . These patches exhibit isotropic behavior when different static and dynamic fields are applied [ 29 ], as demonstrated by placing the patch under a coil and permanent and then rotate the system by 90° while monitoring the vibration behavior. It was shown that rotation had minimal effect on the vibration of the specimen.…”
Section: Experimental Workmentioning
confidence: 99%
“…The magnetostriction phenomenon is widely used for different applications, such as the active element in ultrasonic transducers used to generate elastic waves for nondestructive testing and inspection [ 28 , 29 , 30 , 31 ], microelectromechanical systems or MEMS [ 29 ], positioning sensors [ 32 ], level-gauging sensors [ 33 ] and accurate actuation mechanisms [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation